Reorienting Pesantren Education in East Java: A Critical Analysis of the Thought of Zamakhsyari Dhofier and Abdurrahman Mas'ud - Achmadin, Balya Ziaulhaq; Kawakip, Akhmad Nurul; Nafis, Muhammad Muntahibun; Balah, Abdel Rahman El Sayed Abdel Ghaffar (STAI Serdang Lubuk Pakam, 2024)
Pesantren education is experiencing a paradigm shift that deviates from Arkanul Ma'had due to the times and social changes. This condition requires a reorientation of pesantren education to remain relevant and effective in facing future challenges. This study aims to critically examine the thoughts of Zamakhsyari Dhofier and Abdurahman Mas'ud in the context of reorienting pesantren education in East Java. This research uses a qualitative approach with document analysis as the main method. Through literature study and analysis of the thoughts of Zamakhsyari Dhofier and Abdurahman Mas'ud, this research highlights the relevance and applicability of their thoughts in the context of reorienting pesantren education in East Java. The results revealed that Zamakhsyari Dhofier provided important insights regarding the renewal and adjustment of pesantren curriculum to meet modern needs, while Abdurahman Mas'ud emphasized the importance of integrating religious and general knowledge in pesantren education. The results of this study make a significant contribution to the understanding of the reorientation of pesantren education in this region. The implications of this research can be the basis for policy making and the development of pesantren education strategies that are more effective and relevant to the needs of the times, as well as enriching scientific studies and the treasures of pesantren education in Indonesia.